Case report: Post-streptococcal pustulosis after subcutaneous injection of secukinumab - Lang, Xiaoqing; Bi, Hongmei; Zhang, Yingjie; Cui, Hongzhou; Liu, Hongye; Ren, Ling; Dang, Yao; Guo, Shuping (Frontiers in Medicine, 2023)
A 55-year-old woman sought evaluation of a sore throat, oral erosions, otitis externa, and an acute diffuse pustular eruption due to group A β-hemolytic streptococcus that developed 2 days after receiving a second injection of secukinumab. Group A β-hemolytic streptococcus was isolated from throat swabs. Pustulosisacuta generalisata was definitively diagnosed. Antibiotic treatment had a poor effect, but the response to glucocorticoids was better.